2022
DOI: 10.1002/ajcp.12586
|View full text |Cite
|
Sign up to set email alerts
|

Using a modified version of photovoice in a European cross‐national study on homelessness

Abstract: This study proposes an innovative use of a modified version of photovoice for cross‐national qualitative research that allows participants to express their ideas, experiences, and emotions about a topic through photographic language. We examine factors affecting social service providers' work on people experiencing homelessness in Europe. We highlight five advantages of using photovoice in cross‐national research: visual language, methodological flexibility, participatory data analysis, the bottom‐up process, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Using a multicase photovoice design is a promising avenue to uncover similar issues across settings managed under the same program while also leaving space for local relevance and action. A recent cross‐national photovoice research underlined the value of the method to document services for people experiencing homelessness which could lead to more adequate European guidelines (Gaboardi et al, 2022). Cross‐case findings in the current study led to identifying two specific programmatic issues that should be addressed: problematic maintenance and limited opportunities for tenants' empowerment.…”
Section: Discussionmentioning
confidence: 99%
“…Using a multicase photovoice design is a promising avenue to uncover similar issues across settings managed under the same program while also leaving space for local relevance and action. A recent cross‐national photovoice research underlined the value of the method to document services for people experiencing homelessness which could lead to more adequate European guidelines (Gaboardi et al, 2022). Cross‐case findings in the current study led to identifying two specific programmatic issues that should be addressed: problematic maintenance and limited opportunities for tenants' empowerment.…”
Section: Discussionmentioning
confidence: 99%
“…This research in the European context has identified factors affecting social service providers' work in homeless services comparing HF and TS. In addition to the substantive findings, the cross-national study illustrates a novel method for conducting qualitative research across eight nations with eight different languages (Gaboardi et al, 2022). This new procedure was made possible by the continual interactions among the project's Consortium members, and it was based on a common detailed protocol about planning (aims, recruitment, setting, role of the moderators and assistant, ethics), process (detailed explanation of each step of the photovoice project), and participatory analysis.…”
Section: Limitationsmentioning
confidence: 98%
“…In addition to the many articles above and others about work in one or two countries or even across a continent (e.g., Cheng & Siankam, 2009; Gaboardi et al, 2022; García‐Ramírez et al, 2009; Levine, 1989; Suffla & Seedat, 2015), there have also been AJCP articles and issues that were global in scope or compared countries across different continents. The first of those was Dohrenwend et al (1987) on life stress and psychopathology followed by Gidron et al (1991) on self‐help groups, both articles comparing the US and Israel.…”
Section: Ajcp International Coverage Overtime By Continentmentioning
confidence: 99%